Application of fuzzy fractional kinetic equations to modelling of the acid hydrolysis reaction - Ghaemi, Ferial; Yunus, Robiah; Ahmadian, Ali; Salahshour, Soheil; Suleiman, Mohamed; Saleh, Shanti Faridah (Hindawi Publishing Corporation, 2013)
In view of the usefulness and a great importance of the kinetic equation in specific chemical engineering problems, we discuss the numerical solution of a simple fuzzy fractional kinetic equation applied for the hemicelluloses hydrolysis reaction. The fuzzy approximate solution is derived based on the Legendre polynomials to the fuzzy fractional equation calculus. Moreover, the complete error analysis is explained based on the application of fuzzy Caputo fractional derivative. The main advantage of the present method is its superior accuracy which is obtained by using a limited number of Legendre polynomials. The method is computationally interesting, and the numerical results demonstrate the effectiveness and validity of the method for solving fuzzy fractional differential equations.